Description of Family Support for the Elderly Hypertension - Erni Tri Indarti; Puji Astutik; Binti Jumi Astutik (Master of Public Health Program Universitas STRADA Indonesia, 2024)
One of the most common diseases in the elderly is hypertension. Hypertension, also known as high blood pressure, is a long-term medical condition in which the blood pressure in the arteries is constantly elevated. Lack of adherence and support for hypertension testing is one of the reasons for uncontrolled blood pressure, while family support is the most important factor, especially in terms of health. The purpose of this study was to determine family support for the elderly with hypertension in the elderly Posyandu, Nglaban Hamlet, Nglaban Village, Loceret District. The design of this research a descriptive design, which was conducted on 26th September 2023 at the Posyandu for the elderly in Nglaban Hamlet, Nglaban Village, Loceret District, Nganjuk Regency. The population in this study was 30 hypertensive elderly who attended the Posyandu for the Elderly in Nglaban Hamlet, Nglaban Village, Loceret District, Nganjuk Regency, a sample of 22 respondents taken using the Puprosive sampling technique. The inclusion criteria in this research are hypertensive elderly who live at home with their family. The variable in this study is family support for hypertensive elderly. The instrument used was a questionnaire The results showed that of the 22 respondents, the majority, namely 12 respondents (54.5%), received adequate family support and nearly half, namely 10 respondents (45.5%), received less family support. Family support is needed because it can reduce feelings of anxiety in the elderly, increase enthusiasm for life, involve the elderly in carrying out hypertension treatment so as to obtain the goals of hypertension treatment. So that the family should always provide motivation and support for the elderly with hypertension to make health care efforts and help carry out routine controls in existing health services